Anti-Inflammatory Effects of Concentrated Ethanol Extracts of Edelweiss (Leontopodium alpinum Cass.) Callus Cultures towards Human Keratinocytes and Endothelial Cells. (10th October 2012) - Daniela, Lulli; Alla, Potapovich; Maurelli, Riccardo; Elena, Dellambra; Giovanna, Pressi; Vladimir, Kostyuk; Roberto, Dal Toso; Chiara, De Luca; Saveria, Pastore; Liudmila, Korkina
Abstract : Edelweiss ( Leontopodium alpinum Cass.) is traditionally employed in folk medicine as an anti-inflammatory remedy. In nature, the plant is sparsely available and protected; therefore production of callus cultures was established. A concentrated ethanolic extract of culture homogenate, with leontopodic acid representing 55 ± 2 % of the total phenolic fraction (ECC55), was characterized for anti-inflammatory properties in primary human keratinocytes (PHKs) and endotheliocytes (HUVECs). Inflammatory responses were induced by UVA+UVB, lipopolysaccharide (LPS), oxidized low-density lipoprotein (oxLDL), and a mixture of proinflammatory cytokines. Trichostatin A, a sirtuin inhibitor, was used to induce keratinocyte inflammatory senescence. ECC55 (10–50  μ g/mL) protected PHK from solar UV-driven damage, by enhancing early intracellular levels of nitric oxide, although not affecting UV-induced expression of inflammatory genes. Comparison of the dose-dependent inhibition of chemokine (IL-8, IP-10, MCP-1) and growth factor (GM-CSF) release from PHK activated by TNF α + IFN γ showed that leontopodic acid was mainly responsible for the inhibitory effects of ECC55. Sirtuin-inhibited cell cycle, proliferation, and apoptosis markers were restored by ECC55. The extract inhibited LPS-induced IL-6 and VCAM1 genes in HUVEC, as well as oxLDL-induced selective VCAM1 overexpression. Conclusion. Edelweiss cell cultures could be a valuable source of anti-inflammatory substances potentially applicable for chronic inflammatory skin diseases and bacterial and atherogenic inflammation.